Effect of Ethrel Concentration on Avocado Fruit Running (Persea americana mill) - Erwin Nofiyanto Erwin; Nadhifah .; Dewi Larasati (Universitas Slamet Riyadi Surakarta, 2023)
Avocado is a climacteric fruit, which is usually harvested when it is still unripe. One way to accelerate the maturity of climacteric fruit is by ripening. Ripening treatment with ethrel can accelerate fruit ripening. This study aims to determine the effect of proper ethrel concentration on the avocado ripening process. The experimental design used was RAL (Completely Randomized Design) 1 Factor with 5 treatments and 4 replications. The treatment consisted of P0 control without ethrel treatment, then added ethrel solution P1 = 0.25 ml/L, P2 = 0.50 ml/L, P3 = 0.75 ml/L and P4 = 1.00 ml/L. Variables observed included weight loss, color, texture/hardness, water content, total dissolved solids and fat content. The data obtained were analyzed for variance and if there were significant differences in the treatment then it was further tested with Duncan's test at the 5% level. Based on the results of research on adding the right ethrel solution to the avocado ripening process found in P4 with the addition of 1.00 ml/L ethrel with a fat content of 15.34%, water content 88.99%, total dissolved solids 2.10 mg/L, texture 968.85grf, color 80.44 and weight loss 10.51%.